Design and Analysis of Antireflection Coatings for Silicon Solar Cells using Copper-Nanoparticles - Sharma, R.; Virdi, A. (Journal of Scientific Research, 2025)
Silicon solar cells, despite their widespread use due to their efficiency, cost-effectiveness, and reliability, suffer from low absorption and high reflectance, limiting their performance. In this work an attempt has been made to design a double layer antireflection coating composed of copper-nanoparticles (Cu-NPs) over silicon nitride to study the performance of silicon solar cells. Numerical calculations have been performed using transfer matrix method (TMM) to obtain the reflectance at various values of Cu-NPs radius, gap interval, and volume fraction. The refractive index of the metal nanoparticles used is wavelength dependent. Inclusion of Cu-NPs in the antireflection coating has reduced the reflectance considerably. Calculated reflectance has been used in the PC1D simulator to study performance of silicon solar cell. Results obtained for Cu-NPs based ARC were further compared with a reference cell (without ARC) and a cell with SLARC.